Two distinct populations of Bovine IL-17+ T-cells can be induced and WC1+IL-17+γδ T-cells are effective killers of protozoan parasites - Peckham, R.K.; Brill, R.; Foster, David S.; Bowen, A.L.; Leigh, James A.; Coffey, Tracey J.; Flynn, Robin J. (Nature Publishing Group, 2014)
IL-17 has emerged as a key player in the immune system, exhibiting roles in protection from infectious diseases and promoting inflammation in autoimmunity. Initially thought to be CD4 T-cell-derived, the sources of IL-17 are now known to be varied and belong to both the innate and adaptive arms of the immune system. Mechanisms for inducing IL-17 production in lymphoid cells are thought to rely on appropriate antigenic stimulation in the context of TGF-β1, IL-6 and/or IL-1β. Using culture protocols adapted from human studies, we have effectively induced both bovine CD4+ and WC1+ γδ T-cells to produce IL-17 termed Th17 and γδ17 cells, respectively. The negative regulatory effect of IFN-γ on mouse and human IL-17 production can be extended to the bovine model, as addition of IFN-γ decreases IL-17 production in both cell types. Furthermore we show that infection with the protozoan Neospora caninum will induce fibroblasts to secrete pro-IL-17 factors thereby inducing a γδ17 phenotype that preferentially kills infected target cells. Our study identifies two T-cell sources of IL-17, and is the first to demonstrate a protective effect of IL-17+ T-cells in ruminants. Our findings offer further opportunities for future adjuvants or vaccines which could benefit from inducing these responses.